2018
DOI: 10.1007/s11886-018-1057-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cardiac Magnetic Resonance Imaging in Valvular Heart Disease: Diagnosis, Assessment, and Management

Abstract: Purpose of Review This article will review the current techniques in cardiac magnetic resonance imaging (CMR) for diagnosing and assessing primary valvular heart disease. Recent Findings The recent advancements in CMR have led to an increased role of this modality for qualifying and quantifying various native valve diseases. Phase-contrast velocity encoded imaging is a well-established technique that can be used to quantify aortic and pulmonic flow. This technique, combined with the improved ability for CMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 80 publications
(104 reference statements)
0
33
0
Order By: Relevance
“…The complex anatomy of leak channels preclude the use of the same echocardiography quantification as in native valve regurgitations. Besides, only a moderate agreement between echocardiography and CMR in those parameters using proximal isovelocity surface area (PISA) [ 11 ] was found. Finally, the quality of images (prosthesis) obtained in particular patient affects the measures of severity of PVL, especially in echocardiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex anatomy of leak channels preclude the use of the same echocardiography quantification as in native valve regurgitations. Besides, only a moderate agreement between echocardiography and CMR in those parameters using proximal isovelocity surface area (PISA) [ 11 ] was found. Finally, the quality of images (prosthesis) obtained in particular patient affects the measures of severity of PVL, especially in echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…CMR is considered the gold-standard for these purposes. Although CMR has been validated in the quantitative assessment of some native valve defects [ 10 , 11 ], the evidence supporting the role of CMR in patients with prosthetic valve PVL is scarce and limited to patients with transcatheter aortic valve implantation (TAVI) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though in recent years CMR and CT have been increasingly used for evaluating MV apparatus, especially in the pre-operative or pre-interventional setting [ 19 , 21 ], there is no doubt that 2D/3D TEEs are probably the best modalities for visualizing mitral leaflets. Remarkably, once acquired, 3D volumetric data set can be rotated and angulated, allowing visualization of leaflets in a countless number of perspectives.…”
Section: Mitral Leafletsmentioning
confidence: 99%
“…In mice S. aureus-induced IE can be detected using MRI technology [20]. A review of the benefit of cardiac MRI found an increasing role in the diagnosis of valvular lesions, though vegetations can be easily missed due to the fine imaging slices used in cine [21]. In a small singlecentre study in Turkey cardiac MRI was requested on 16 patients with presumed IE to obtain additional information, particularly in six patients who had been unable to complete a TOE [22].…”
Section: Infective Endocarditismentioning
confidence: 99%